ANALYSIS OF INFLUENCE OF BRAND IMAGE, QUALITY PRODUCT, AND PRICE FOR REPURCHASE ORIFLAME PRODUCTS IN KAB. KARAWANG - Yulianti, Tati; Suyaman, Dede Jajang; Solehudin, Solehudin (Jurnal Ekonomi Manajemen, 2023)
This study aims to determine the relationship between brand image and product quality, product quality and price, and brand image and price on Oriflame products. Price on Repeat Purchase of Oriflame Products, Simultaneous Influence between Brand Image, Product Quality and Price on Repeat Purchase of Oriflame Products. This research was conducted using a quantitative method with a descriptive and verification approach and the sample used Hair et al and a porposive sampling technique which then produced a sample of 180 respondents. The analysis technique used is the Likert scale analysis technique and path analysis with the Method of Successive Interval (MSI), Microsoft Office, and SPSS version 18.0. There is a partial effect of brand image on product repurchase, product quality has a partial and significant effect on product repurchase. There is a partial and significant price effect on product repurchases. Simultaneously brand image, product quality and price affect the repurchase of Oriflame products